Religious fundamentalism, religiosity, and priming: effects on attitudes, perceptions, and mock jurors’ decisions in an insanity defense case - Yelderman, Logan A. (Psychology, crime & law, 2017)
Jurors are asked to use their personal knowledge and experience to make verdict decisions; thus, it is no surprise that their religious beliefs might influence their decisions. During legal insanity trials, jurors might also be exposed to religious stimuli (e.g. crucifix, prayer, Bible, etc.), which could evoke (prime) religious beliefs and thus influence decisions. Two studies examined whether dimensions of religiosity and religious beliefs relate to attitudes and decisions concerning mental health defenses, testing social identity theory against Allport and Ross’s religiosity hypothesis. In Study 1 (attitudes survey) and Study 2 (mock juror decision-making paradigm), religious fundamentalist beliefs consistently predicted punitive attitudes and decisions related to mental health defenses and verdicts, and this was moderated by intrinsic religiosity, such that religious fundamentalist beliefs only predicted punitiveness for individuals low in intrinsic religiosity. Also, priming fundamentalist beliefs increased punitiveness in both verdict and sentencing decisions. Combined, these results suggest that religious beliefs play a role in jurors’ verdict decisions in an insanity case, and that priming fundamentalist beliefs increases jurors’ punitiveness. Allport and Ross’s religiosity hypothesis was supported, but social identity theory was not.